Germans' awareness of refugees' information barriers regarding health care access: a cross-sectional study - Saskia Schubert; Ulrike Kluge; Felix Klapprott; Tobias Ringeisen (BMC, 2023)
Abstract Background In light of their experiences on the refuge and upon their arrival in the receiving society, refugees may have differentiated needs regarding health care. However, negative attitudes of the members of the receiving society and a lack of information pose as barriers for refugees when trying to access health care services. In that sense, it is largely unknown, which antecedents positively affect Germans' perception of information barriers that refugees face. Based on an extended version of the Empathy-Attitude-Action model, this study examined selected predictors of problem awareness in the form of perceived information barriers that refugees face, emphasizing the role of positive intercultural contact experiences. Methods A sample of members of the receiving society, here: Germans (N = 910) completed a cross-sectional online survey with validated self-report measures. From the perspective of Germans, assessments covered positive intercultural contact, attitudes on refugees' rights, the recognition of refugees' socio-emotional support needs as a form of cognitive empathy, and the perception of refugees' information barriers when accessing health care. We conducted structural equation modeling to examine hypothesized latent associations and specified three different models with unidirectional paths between the study variables, each allowing another direct path from intercultural contact to the variables. We determined the best model using the chi-square-difference test and tested for indirect effects along the paths through bias-corrected bootstrapping. Results Our results show consistency with the Empathy-Attitude-Action model. We found Germans' cognitive empathy toward refugees to be associated with more positive attitudes and a greater awareness of refugees' information barriers. We further found more positive intercultural contact to be associated with greater cognitive empathy toward refugees and with more positive attitudes. While these contact experiences showed a slightly direct negative effect on Germans' perception of refugees' information barriers to accessing health care, the indirect effects via cognitive empathy and positive attitudes were positive. Conclusion Previous positive intercultural contact may be directly and indirectly linked to greater awareness for refugees, helping Germans as the receiving community (1) to become more empathetic toward refugees, (2) to improve their attitudes toward refugees' rights and to (3) raise consciousness for information barriers that refugees face when trying to access health care services.